Use of several systems of herbicide application in cotton (Gossypium hirsutum) culture - FALONI, LUIZ LONARDONI; RODRIGUES, JOÃO DOMINGOS; ONO, ELIZABETH ORIKA; TAKAMOTO, HELIO (Revista Ceres, 2015)
.